An evaluation of proper inhaler technique and adherence to treatment in asthma patients - P., Abdul Hashim K.; Ayoob, Muhammed Anas (International Journal of Research in Medical Sciences, 2019)
Background: Medications used to manage Asthma is delivered via inhaler devices. Proper usage of these devices are required for effective medication delivery. Aim of this study is assess the degree of proper inhaler technique and adherence to treatment among adult asthma patients. Methods: Patients using inhalers were identified and interviewed regarding inhaler use. Checklists were used to document the adherence to manufacturers’ directions for each respective inhaler, and data were then tabulated and assessed for the types of inhalers used, incorrectly performed steps in using the inhalers, as well as demographic information of patients. Results: Out of 120 patients that taken as subjects, twenty-four percent of inhalers (29/120) used incorrectly, with the most common errors being improper priming, lack of proper exhalation prior to inhaling the medication, and absence of rinsing mouth following the use of inhaled corticosteroid. Furthermore, only 60% of the patients are adherent to asthma medications. Conclusions: Inhaler technique among adult patients is substandard and is considered a key area for physicians to more proactive in educating patients. For obtaining most accurate therapeutic advantage among patients with inhalers, proper instruction and demonstration regarding inhaler use need to be given to all patients, particularly elderly patients.